Biblical argument in Manichaean missionary practice : the case of Adimantus and Augustine - Berg, Jacob Albert van den, 1975- (Nag Hammadi and Manichaean Studies, 2010)
The use and appreciation of Scripture by the Manichaeans is a field of research with many unanswered questions. This study offers an investigation into the role of the Bible in the writings of the important Manichaean missionary Addas Adimantus (flor. circa 250 CE), one of Mani's first disciples. A major part of the book is dedicated to the reconstruction of the contents of his Disputationes, in which writing Adimantus attempted to demonstrate that the Old and New Testaments are absolutely irreconcilable. The most important source in this connection is Augustine, who refuted a Latin translation of Adimantus' work. A thorough analysis of the contents of the Disputationes brings to the fore that Adimantus was a Marcionite prior to his going over to Mani's church.